THE INVESTIGATION OF NANO ULTRAVIOLET LIGHT EFFICIENCY ON DISINFECTION OF STETHOSCOPES - Akbulut, Ayhan; Cagasar, Ozlem; Ozden, Mehmet; Akbulut, Hatice Handan; Demirdag, Kudbettin (Nobel Ilac, 2013)
Objective: Medical devices such as stethoscopes play an important role in the development of hospital infections and transport of pathogenic microorganisms. In this study disinfection efficiency of nano ultraviolet light which had been applied to stethoscopes was investigated. Material and Method: In various clinical units nurses desk and the doctor stethoscopes cultures were taken before implementation. After disinfection with nano ultraviolet light, cultures were repeated. Identification of the samples was done after incubation for 24-48 hours, colony counts and antibiotic susceptibilities were determined. Results: Bacterial growth was detected in all stethoscope cultures which had been taken before disinfection. Polimicrobial growth was occured in 9 (%16,4) of stethoscopes. A significant decrease in the number of MRKNS (Methicillin-resistant Coagulase Negative Staphylococci), MSKNS (Methicillin-sensitive Coagulase Negative Staphylococci) and MRSA (Methicillin-resistant Staphylococcus aureus) colonies was seen in the cultures which had been taken after disinfection (p<0.05). Reduction in the number of MSSA (Methicillin-sensitive Staphylococcus aureus) colonies were determined but not this decline statistically significant (p=0.36). Conclusion: Disinfection of stethoscope with nano ultraviolet light was observed to be effective to prevent hospital infections as defined nosocomial infections and to prevent transferring resistant microorganisms from hospital to environment and community. Especially using of nano ultraviolet light was supposed to take place in infection control because of rapid disinfection of stethoscope.
Keywords: Stethoscope; nano-ultraviolet light; disinfection; nosocomial infection